Digital Transformation through the Prism of Digital Identity - Malik, Tariq (Journal of Public Policy Practitioners, 2022)
Breakthroughs in digital technologies have notably helped to enhance the capability of administrative systems across the globe and allowed precision and effectiveness in governance mechanisms like never before. The current study attempted to build around three critical aspects of governance, that is, lack of state capacity, trust deficit between citizen and state (empowerment), and poor service delivery. The study elaborated how the use of biometrics and smart technologies enhances public service delivery and revitalises trust of citizens in the state. It is a qualitative research based on observations, case studies, and real world examples to link national citizens’ registry to various disparate repositories and use it innovatively in order to reform governance. Its manifestations are manifolds, for instance, from empowering persons to avail public health services and financial inclusion to create value for private sector through market, creating innovations, that is, National Database and Registration Authority (NADRA). It has fortified digital governance framework in Pakistan by the virtue of legal identity. The success story of NADRA provides guidelines to developing countries that how organisations could be turned around by employing technologically innovative and culturally targeted approach towards public policy and digital governance initiatives.